The Art of Questioning in Online Learning: Effective Questioning Strategies in EFL Reading Class - Siti Yulidhar Harunasari; Soepriyatna Soepriyatna; Nita Fitriani; Ellen Juita Gultom (Universitas PGRI Semarang, 2023)
The advent of online learning has made it necessary for educators to develop new teaching strategies, particularly in the area of questioning techniques. This study aimed to explore the types of questioning strategies employed by teachers during online reading classes and identify the factors that contribute to the frequent use of a specific approach. The study used observation checklists and interview guidelines based on Bloom's taxonomy and Wragg and Brown's questioning strategies to gather data from second-year English language students enrolled in an online reading class. The research findings revealed that to engage students, evaluate their comprehension, and ensure alignment with the textbook material the teacher primarily utilized